Connect to nature; a home for well being where indoor and outdoor are connected - Pettersson, Johanna (My University, 2024)
In healthcare environments the contact with nature has positive impacts on health and well-being, which previous studies have shown. Contact with nature reduces stress, anxiety and the feeling of isolation and promotes healing and recovery. Outdoor environments contribute to social activities, connection to the society, stimulate physical activity, and a varied rehabilitation. For elderly people in healthcare environments the contact with nature is therefore important, but today many elderly at Swedish nursing homes feel a limitation in the access to outdoor environments. The design choices contribute to the contact to nature and the possibility to use the outdoor environments, and it already starts from inside the building. In my master’s thesis I have developed a proposal for a nursing home in Örebro, where the design decisions enhancing the contact to the nature and the surrounding. The aim has been to design a proposal where the architecture strengthens the connection between the indoor and outdoor environments to offer various choices and contribute to well-being for the elderly. The aim has been to encourage and facilitate outdoor stay and create preconditions for activities outdoor. The aim has also been to design a home where the contact with nature and the surrounding is clear even when staying indoor. To connect the indoor and outdoor environment, accessibility, the target group, movement, visual connection, and the impact of nature has been studied. One conclusion is that the outdoor environments need to be close and adapted to the target group to enable outdoor stay. The building and the outdoor environment need to interact to take advantage of the positive effects that the nature and the outdoor environment can contribute to. Also, the indoor environment can offer various dimensions of contact with nature. To connect the indoor and outdoor environment, a variety in the design is required as the elderly have different abilities, needs and interests. The method consists of research by literature studies, interviews, and study visits where the connection between architecture, nature, and health(care) is studied. These was the basis for the design studies which then landed in a final design proposal.
Keywords: Connecting indoor and outdoor, health-promoting design, well-being, nature, nursing home